A Proactive Outreach Strategy Using a Local Area Code to Refer Unassisted Smokers in a Safety Net Health System to a Quitline: A Pragmatic Randomized Trial. Issue 1 (14th September 2022) - Valencia, Cindy V; Dove, Melanie S; Cummins, Sharon E; Kirby, Carrie; Zhu, Shu-Hong; Giboney, Paul; Yee, Hal F; Tu, Shin-Ping; Tong, Elisa K
Abstract: Introduction: Proactive outreach offering tobacco treatment is a promising strategy outside of clinical settings, but little is known about factors for engagement. The study objective is to examine the impact of caller area code in a proactive, phone-based outreach strategy on consenting low-income smokers to a quitline e-referral. Aims and Methods: This pragmatic randomized trial included unassisted adult smokers ( n  = 685), whose preferred language was English or Spanish, in a Los Angeles safety-net health system. Patients were randomized to receive a call from a local or generic toll-free area code. Log-binomial regression was used to examine the association between area code and consent to a quitline e-referral, adjusted for age, gender, language, and year. Results: Overall, 52.1% of the patients were contacted and, among those contacted, 30% consented to a referral. The contact rate was higher for the local versus generic area code, although not statistically significant (55.6% vs. 48.7%, p  = .07). The consent rate was higher in the local versus generic area code group (adjusted prevalence ratio 1.29, 95% CI 1.01–1.65) and also higher for patients under 61 years old than over (adjusted prevalence ratio 1.47, 95% CI 1.07–2.01), and Spanish-speaking than English-speaking patients (adjusted prevalence ratio 1.40, 95% CI 1.05–1.86). Conclusions: Proactive phone-based outreach to unassisted smokers in a safety net health system increased consent to a quitline referral when local (vs. generic) area codes were used to contact patients. While contact rate did not differ by area code, proactive phone-based outreach was effective for engaging younger and Spanish-speaking smokers. Implications: Population-based proactive phone-based outreach from a caller with a local area code to unassisted smokers in a safety net health system increases consent to an e-referral for quitline services. Findings suggest that a proactive phone-based outreach, a population-based strategy, is an effective strategy to build on the visit-based model and offer services to tobacco users, regardless of the motivational levels to quit.